Analyzing Intervening Coping Measures for Stress Abatement: A Perceptual Study - Ch. , Narahari; Koneru, Kalpana (International Journal of Psychosocial Rehabilitation, 2020)
In the present study we analyze the employees’ perception towards coping measures adopted by firms in the software industry. The considered coping constructs adopted for the study in stress abatement are venting of emotions, problem-focused, seeking information and emotional support, and positive emotion-focused, where employee perception was acquired by a systematic survey. A total sample of 800 employees’ perceptions has been collected through a simple random technique, and out of which survey respondents, irregular responses are eliminated; finally, 756 samples are determined for statistical analysis. A chi-square test was performed to determine the association between perceptions and model constructs. Results are reported, and discussions are made as per the results and in correlation with the results of previous literature. Finally, suggestions and future indications for extension of the study are proposed.